Penerapan Teknologi Hijau untuk Pengelolaan Limbah dalam Mendukung Ekonomi Berkelanjutan - Perdana, Panji; Hadinata, Farhan (Innovative: Journal Of Social Science Research, 2025)
Urban solid waste management poses a significant challenge in supporting sustainable development, particularly in developing countries like Indonesia. This study aims to evaluate the implementation of waste-to-energy (WtE) technology based on biogas in waste management facilities in Jakarta and Surabaya. The methodology employed includes a literature review and secondary data analysis from scientific journals, technical reports, and policy documents. The results indicate that WtE technology can reduce carbon emissions by up to 30% compared to conventional waste management methods, while also generating energy that meets 10-15% of local energy needs. Additionally, the adoption of this technology has the potential to create new economic opportunities by increasing the added value of processed waste. However, key challenges identified include high initial investment costs, limited local technological capacity, and insufficient support through incentive policies. This study recommends collaboration among governments, the private sector, and communities to accelerate the adoption of WtE technology, including fiscal incentives, technology transfer, and enhanced technical capacity. With these strategies, WtE technology can serve as an effective solution for more sustainable urban waste management.